Pengaruh Teknik Relaksasi Genggam Jari Terhadap Penurunan Nyeri Pada Pasien Post Sectio Caesarea Di Rumah Sakit TK.II R.W Mongisidi Manado - Dewi Astuti Sudijanto; Cut Mutya Bunsal; Berthina Hermin Korah (Jurnal Anestesi, 2023)
Labor is the process of opening and thinning the cervix, where the fetus is pushed out through the birth canal. Finger Grip Relaxation is a muscle relaxation action that is believed to reduced pain. The purpose of this research was to find out the effect of finger grip relaxation technique on pain reduction in post sectio caesarea patients at the 2nd Grade Hospital of R.W. Monginsidi in Manado.This research was conducted by using a quasi experimental one group pre-test and posttest design. Sampel in this research amounted to 15 respondents using accidental sampling technique. Data collection was done by sharing SOP. Then, the collected data was processed by running the SPSS computer program version 16.0 to be analyzed by a Wilcoxon test with the significance level ? = 0,05.The result showed that there is an effect of finger grip relaxation technique on pain reduction in post sectio caesarea patients.The conclusion of this research is that there is an effect of finger grip relaxation technique on pain reduction in post sectio caesarea patients at the 2nd Grade Hospital of R.W. Monginsidi in Manado. It is suggested to update information about the effect of finger grip relaxation technique on pain reduction in post sectio caesarea patients.